2018
DOI: 10.1111/1759-7714.12631
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of circulating tumor cells in patients with EGFR‐mutated or ALK‐rearranged non‐small cell lung cancer

Abstract: BackgroundCirculating tumor cell (CTC) counts at baseline and follow‐up are an independent prognostic factor in patients receiving standard chemotherapy for non‐small cell lung cancer (NSCLC). This study further explored the role of CTCs in EGFR‐mutated and ALK‐rearranged NSCLC patients administered targeted therapies as first‐line treatment.MethodsCTCs were enumerated with a novel high‐efficiency detection method from the blood of 43 patients with EGFR‐mutated or ALK‐rearranged NSCLC at baseline and at diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Such data support the notion that CTCs can simultaneously provide an overview of tumor genomics and gene expression, and that the characterization of CTCs may be a key factor as these cells are ultimately responsible for metastasis [90]. CTC counts work as independent prognostic factors at both baseline and during follow-up in patients with EGFR-mutated or ALK-rearranged NSCLCs undergoing standard chemotherapy or targeted therapies [102]. In patients with metastatic cancer receiving systemic treatment, temporal changes in the number of CTCs have been shown to correlate with clinical outcome, as measured by standard radiography [103].…”
Section: Liquid Biopsy In Monitoring Response To Treatmentsupporting
confidence: 56%
“…Such data support the notion that CTCs can simultaneously provide an overview of tumor genomics and gene expression, and that the characterization of CTCs may be a key factor as these cells are ultimately responsible for metastasis [90]. CTC counts work as independent prognostic factors at both baseline and during follow-up in patients with EGFR-mutated or ALK-rearranged NSCLCs undergoing standard chemotherapy or targeted therapies [102]. In patients with metastatic cancer receiving systemic treatment, temporal changes in the number of CTCs have been shown to correlate with clinical outcome, as measured by standard radiography [103].…”
Section: Liquid Biopsy In Monitoring Response To Treatmentsupporting
confidence: 56%
“…In many types of cancer, including osteosarcoma, overexpression of EGFR is associated with aggressive invasiveness and resistance to therapy (24)(25)(26). Previous studies have indicated that EGFR may be an effective target for the treatment of human cancer (27,28). The US Food and Drug Administration has approved five anti-EGFR agents for cancer treatment including three small molecule inhibitors and two .…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the progressive discovery of different mutations in several genes involved in different biological processes regulating lung cancer development and progression. As an example, epidermal growth factor receptor (EGFR) [29], anaplastyc lymphoma kinase (ALK) [30], and Kirsten rat sarcoma viral oncogene homolog (K-RAS) [31] mutations, are considered prognostic and predictive biomarkers and targets for personalized drugs [32, 33]. In this context, the use of miRNA therapeutics as “next generation targeted drugs” seems to be promising [34].…”
Section: Resultsmentioning
confidence: 99%